Fault diagnosis of the distribution network based on the D-S evidence theory Bayesian network - Wu, Xiaogang; Zhao, Hanying; Xu, Wentao; Pan, Wulue; Ji, Qingfeng; Hua, Xiujuan (Frontiers in Energy Research, 2024)
There are relay protection rejection and misoperation in the existing distribution network, which will affect the fault diagnosis results. To diagnose faults in distribution networks, this paper presents a fault diagnosis method for distribution network based on D-S evidence theory Bayesian network. Firstly, the collected relay protection information is divided into two categories: protection information and circuit breaker information, and the corresponding Bayesian network model is established based on their respective action logic, and the corresponding component failure probability is obtained by Bayesian backward inference. Secondly, the fault probabilities obtained from the two Bayesian networks are fused by the D-S evidence theory, and the obtained fault probabilities are used to diagnose the faulty component. Then using the Bayesian network corresponding to the faulty component to perform Bayesian forward inference, identifying the protection devices and circuit breakers for misoperation or rejection to achieve fault diagnosis of distribution network. Finally, the correctness and reliability of the proposed diagnosis method are verified through the analysis of arithmetic cases.